Investigation the Correlation of Burnout with Mental Health in Medical Staff of the Valyasr Hospital in Borujen - mohammad heidari; Pejman Hassani; mansureh ghodusi (Tehran University of Medical Sciences, 2015)
Background:Job burnout is an issue which often affects personnel`s mental health and quality of services in health systems. This study is aimed to investigate the correlation between burnout and mental health in medical staffs of Valyasr hospital in Borujene due the physical and mental health`s importance of hospitals personnel. Materials and Methods: This is a descriptive and cross-sectional study which has been conducted during the year of 1391. 133 medical personnel of the Valy Asr hospital had been selected by census. All clinical personnel had been participated in the survey apart from physician.A triple questionnaire including demographic information, general health and questions of Maslach Burnout Inventory  questionnaire had been used for data collection.The data had been analyzed by ANOVA, Spearman correlation coefficient, chi-square test and SPSS (version 16). Results: The findings revealed that majority of Personnel involved in the survey felt a distinct lack of personal accomplishment and they showed symptoms of mental disorders. Few personnel showed a distinct emotional exhaustion. More than two-thirds of the patients showed mild depersonalization. Significant reverse correlation had been observed between all dimensions of burnout and mental health. Conclusion:The medical profession has a stressful and arduous  nature.As survey`s findings point to  high prevalence of psychological disorders and reverse correlation between mental health and job burnout , it is highly recommended that managers identify sources of stress and plan for applying preventive interventions and solving current problems.